Understanding Institutional Influences on MSMEs' Environmental Accounting Adoption - Sukma Uli Nuha; Ria Meilan; Bahodirovich , Khalilov Bahromjon (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The Sustainable Development Goals (SDGs) are a global agenda that demands the active involvement of all sectors, including micro, small, and medium-sized enterprises (MSMEs). MSMEs make a significant contribution to economic growth; however, awareness and implementation of sustainability practices, particularly environmental accounting practices, remain relatively low. Specific Background: Previous studies have focused primarily on large companies, resulting in a limited understanding of the drivers (antecedents) of environmental accounting practices in MSMEs. Knowledge Gap: the need for a theoretical approach that can explain how institutional pressures (normative, coercive, and mimetic) can influence the environmental accounting behaviour of MSMEs. Objective: This study examines the antecedents of environmental accounting practices among MSME business actors to create a sustainable business. Methods: A qualitative approach was employed to analyze data on the direct and indirect drivers of the behavior of all MSMEs engaged in the food and beverage processing sector in East Java Province, as well as a sample of MSMEs in Lumajang District and Gresik District, to inform environmental accounting practices. Results: Provides empirical evidence on the direct and indirect drivers of the behaviour of ​​ MSMEs in ecological accounting practices. MSMEs in Indonesia achieve business sustainability through institutional mechanisms, driven by coercive, normative, and mimetic pressures. Novelty: This study explains the drivers of MSMEs' ​​ behaviour towards environmental accounting practices based on institutional theory mechanisms. Implication: This study suggests that MSMEs should adopt environmental accounting practices to promote sustainable development.